Upaya Pencegahan dan Pengendalian Penyakit Jantung Koroner Berbasis Rumah Sakit: Literatur Review - Azzahra', Lama'ah (JURNAL MEDIKA USADA, 2024)
Background: Deaths from Coronary Heart Disease are still a major problem in the world, including in Indonesia. CHD is also a health problem that can have a socio-economic impact. Purpose: This study aimed to determine how prevention and control efforts can be made for people with hospital-based Coronary Heart Disease. Methods: This type of research was a literature review of several articles that have been comprehensively collected through Google Scholar, Springerlink, ScienceDirect by using keywords in the literature search was "intervention AND coronary heart disease AND hospital-based". Result: From the 6 articles that have been analyzed and understood in depth, it was found that there were several forms of hospital-based CHD prevention and control efforts that can be carried out by CHD sufferers ranging from routine blood pressure control and heart health checks, establishing health promotion clinics, conducting education by utilizing waiting rooms and open spaces in hospitals, management of LDL and non-HDL cholesterol increases early on, hospital-based CHD rehabilitation (Phases 1-3), availability of remote cardiac rehabilitation practices and digital therapeutics. Conclusion: Overall, these efforts are expected to improve the quality of life, psychological well-being, cardiovascular capacity, social support and adherence of CHD patients and other communities to CHD rehabilitation programs. CHD prevention and control efforts also need to be implemented in primary care centers, especially in rural areas with inadequate medical and health resources.